Prevalence of impacted third maxillary molar tooth with skeletal malocclusion reviewed from cephalometric imaging in RSGM Kandea and Ladokgi Makassar year 2016-2019: Prevalensi impaksi gigi molar ketiga rahang atas disertai maloklusi skeletal ditinjau dari gambaran sefalometri di RSGM Unhas dan Ladokgi Makassar tahun 2016-2019 - Barunawaty Yunus; Kenrico John Nursalim; Andi Sumidarti (Makassar Dental Journal PDGI Makassar, 2022)
Background: Radiography is an inseparable part of dentistry, one of which is cephalometric techniques. Impacted tooth is a con-dition of the tooth that cannot erupt completely; whereas malocclusion is a mismatch between the two jaws. Objective: To de-termine the prevalence of maxillary third molars with skeletal malocclusion at Hasanuddin University Hospital and Ladokgi Ma-kassar Hospital. Methods: This descriptive observational research used total sampling research design. The population are all cephalometric radiographic data of patients aged 17-30 years collected from medical record data years 2016-2019. The data are processed in tables. Results: A total of 45 (56.3%) samples were impacted and 35 (43.8%) samples were not impacted. Class I skeletal malocclusion is the most common in all impaction cases and women are more prevalence than men. The group of 20-22 years was the most affected sample. The most common angulation is distoangular. Conclusion: Maxillary third molar im-paction with skeletal malocclusion was more common in women, in the age group 20-22 years, with the most impacted angulati-on being distoangular. Class I skeletal malocclusions were the most common in the sample, followed by Class II, and Class III.